Corporate social responsibilty projects and effect of participating to csr projects on employee self-esteem - Miskoen, Betina (My University, 2006)
KURUMSAL SOSYAL SORUMLULUK PROJELERI VE BU PROJELERE KATILAN CALISANLARIN OZGUVENLERI Bu projenin amaci, okuyucuyu Kurumsal Sosyal Sorumluluk Projeleri hakkinda bilgilendirmek, özgüven ile KSS Projelerine katilim arasındaki korelasyonu ampirik olarak test etmek ve KSS Projelerine katilim ile calisan ozguveni arasinda pozitif bir iliski varsa bunu ortaya cikarmaktir. Bu arastirma icin secilen yontem kantitatiftir. Ilac sektoru arastirma alani olarak secilmistir. Turkiye’de faaliyet gosteren ve sosyal sorumluluk projelerine yatirimda bulunan, ayni zamanda AIFD uyesi olan Uluslararasi Ilac Firmalari analiz edilmistir. Arastirma Pfizer Ilaclari Ltd. Sti.’de uygulanmistir. Orneklem, Pfizer bunyesinde yer alan “Toplum Takımı”nda bugune kadar calismis ve bugune kadar hic calismamis olmak uzere toplam 128 kisiden olusmaktadir. Factor analizi uygulanmistir. ASSEI skorlari varyans analizi ve t testi ile olculmus, bununla birlikte demografik faktorlerle kurulan iliskilere de yer verilmistir. Bulgulara göre; sosyal sorumluluk projelerine katılan calisanlarin ozguvene ait bazi faktorlerde daha yuksek skorlar aldigi gorulmustur. Bu faktorler sosyal benlik, materyal benlik, kisisek basar ve gurur duyan benlik faktorleriyle iliskilidir.

CORPORATE SOCIAL RESPONSIBILITY PROJECTS AND SELF ESTEEM OF EMPLOYEES WORKING ON THESE PROJECTS The aim of this research is to inform the reader about Corporate Social Responsibility Projects and empirically test the correlation between employees’ self-esteem and participation to CSR projects and find out if there is significant positive relation between participation to CSR Projects and employees’ self-esteem. Quantitative method is selected for this research. Pharmaceutical sector is selected as the research area. Multinational Pharmaceutical Companies that are a member of AIFD (Researcher Pharmaceutical Companies Community) operating in Turkey and investing on CSR Projects are being analyzed in this research. The research is implemented at Pfizer Pharmaceutical Company. Sample consists of 64 employees who still work at Pfizer and are or have been a member of “Corporate Team” before and the other 64 employees are the control group who have not participated this team yet. Factor analysis is implemented. ASSEI scores are measured by variance analysis and t-test with respect to demographic attributes. Upon the findings, we can state that employees who have participated to CSR Projects obtained higher scores on some of the items of self – esteem. These items are related to social self, material self, personal achievement and appreciated self components.
Keywords: Özgüven, Çalışanların_İşletmeler; Sosyal Sorumluluk, İşletmelerin